2012
DOI: 10.1179/1351000212y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of superoxide generation and cytotoxicity in neuroblastoma mitochondria induced by 1-trichloromethyl-1,2,3,4-tetrahydro-beta-carboline

Abstract: The potential neurotoxin 1-trichloromethyl-1,2,3,4-tetrahydro-beta-carboline (TaClo) has recently been suggested to be a causative factor in the clinical development of parkinsonian symptoms after long-term exposure to precursor compounds such as the hypnotic chloral hydrate. TaClo is known to cause cell death in dopaminergic neuronal cells, however, the pathway and mechanisms remain undefined. This study reports for the first time that TaClo promotes cytotoxicity in SH-SY5Y neuroblastoma cells within 2 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…On the one hand, B-CA can undergo an N-methylation reaction on the second position, and the derived compound is an analogue of the 1-methyl-4-phenylpyridinium ion (MPP+), which can have mitochondrial cytotoxic effects, since its accumulation can lead to oxidative stress, which blocks the complex I of the mitochondrial electrons transport chain [89]. Diversely, some researchers suggested that B-CA has anti-oxidant properties against reactive oxygen species (ROS), possibly reducing cell damage [78].…”
Section: β-Carbolines Alkaloidsmentioning
confidence: 99%
“…On the one hand, B-CA can undergo an N-methylation reaction on the second position, and the derived compound is an analogue of the 1-methyl-4-phenylpyridinium ion (MPP+), which can have mitochondrial cytotoxic effects, since its accumulation can lead to oxidative stress, which blocks the complex I of the mitochondrial electrons transport chain [89]. Diversely, some researchers suggested that B-CA has anti-oxidant properties against reactive oxygen species (ROS), possibly reducing cell damage [78].…”
Section: β-Carbolines Alkaloidsmentioning
confidence: 99%
“…They were able to establish the transmembrane flux of superoxide anions into the extracellular space through voltage-dependent anion channels (VDACs), in other words, key neurotransmission elements. Boulton et al [22] evaluated the neurotoxicity of 1trichloromethyl-1,2,3,4-tetrahydro-beta-carboline (TaClo) in SH-SY5Y neuroblastoma cells by assaying superoxide production from isolated mitochondria with an amperometric biosensor. It should be noted, however, that, contrary to our approach, this method required the fractionation of cellular organelles and as such could not be used for continuous monitoring of superoxide anion production from intact cells.…”
Section: Journal Of Sensorsmentioning
confidence: 99%
“…However, it should be noted that the role of complex II appears to be greater than previously assumed even in liver as portrayed by the 3NP results. The addition of this other commonly used complex II inhibitor shows a degree of inhibition which is comparable to that observed using the other complex I inhibitor TaClo [28]. Interestingly, although 3NP is a well-documented RC inhibitor, the emphasis in the literature in terms of numbers of studies remains biased towards the complex I and III inhibitors, rotenone and antimycin, with an additional focus on (rat) liver and muscle studies as opposed to skin.…”
Section: Resultsmentioning
confidence: 60%